Short Italian Wilkins Rate of Reading Test for repeated-measures designs in optometry and neuropsychology - De Luca, Maria; Nardo, Davide; Rizzo, Giulia Carlotta; Daini, Roberta; Tavazzi, Silvia; Zeri, Fabrizio (Frontiers in Psychology, 2024)
Background: The recently published New Italian version of the Wilkins Rate of Reading Test (standard Italian WRRT) was designed to measure reading speed in repeated-measures designs in research and/or clinical examinations. The test features 15 equivalent 10-line passages made up of unrelated words, adhering to the principles established by the Wilkins Rate of Reading Test in English (original WRRT). Aim: To develop a short Italian version of the WRRT (SI-WRRT), and to determine the equivalence across the new, shorter passages of text. The introduction of 5-line passages, instead of the original 10-line ones, aims to enhance the tool's suitability for the elderly or neuropsychological patients by reducing administration time.The same fifteen high-frequency Italian words from the standard Italian WRRT were used to generate 15 5-line passages for the SI-WRRT. Comprehensive eye examination and vision assessment, including the Radner Reading Charts, were performed before the administration of the SI-WRRT. Forty healthy Italian-speaking higher education students read the SI-WRRT passages aloud in random order. Reading speed and accuracy were measured offline from digital recordings of the readings. Equivalence across passages and the effects of practice and fatigue were assessed for reading speed and accuracy, along with test-retest reliability.Results: No significant difference in reading speed was found across 14 out of the 15 passages.In addition, no differences were observed in accuracy, and the error rate was very low. Practice and fatigue effects were minimal for reading speed, whereas they were absent for accuracy.Reading speed, the reference metric for the WRRT, showed moderate-to-good test-retest reliability.Equivalence was confirmed across fourteen passages of the SI-WRRT. Therefore, the test may be suitable for examining the elderly or neuropsychological patients, as reading time of the 5-line passages is halved with respect to the standard Italian WRRT. However, the 5-line passages still allow the assessment of prolonged reading. Since one passage was not equivalent, we recommend avoiding the use of random rearrangements of words without formally checking their validity.